Efficacy and Safety of a Colic Relief Remedy in Infantile Colic - Charles Evans MD; Wladimir P. Lorentz MD (SAGE Publishing, 2022)
Infantile colic is the most frequent reason of infant and parental distress. An open-label single-group clinical study was conducted primarily to evaluate the effect of 14-day colic relief remedy administration (1.25 ml orally during colic episode) on average daily crying time in infants compared to baseline. In addition, the percentage of responders, sleep pattern, frequency and severity of gastrointestinal symptoms, tolerability of the product and percentage population with relapse of symptoms post product discontinuation were evaluated. Thirty infants aged 3 to 16 weeks with no significant clinical illness were enrolled in the study with their caregivers. Daily inconsolable crying time and flatulence were significantly reduced ( P < .05) within a week of intervention and a sustained effect was observed after discontinuation of the product. The findings of the present study indicate that this product effectively reduced abdominal distension and pain, resulting in a significant decrease in the daily crying of the infants. Trial registration: The study was registered with the Clinical Trials Registry India (CTRI) ( http://ctri.nic.in/Clinicaltrials/login.php ) bearing Reg. No: CTRI/2021/03/031762, Date: March 8, 2021.